Mesocorticolimbic Dopamine Pathways Across Adolescence: Diversity in Development - Reynolds, Lauren M.; Flores, Cecilia (Frontiers in neural circuits, 2021)
Mesocorticolimbic dopamine circuity undergoes a protracted maturation during adolescent life. Stable adult levels of behavioral functioning in reward, motivational, and cognitive domains are established as these pathways are refined, however, their extended developmental window also leaves them vulnerable to perturbation by environmental factors. In this review, we highlight recent advances in understanding the mechanisms underlying dopamine pathway development in the adolescent brain, and how the environment influences these processes to establish or disrupt neurocircuit diversity. We further integrate these recent studies into the larger historical framework of anatomical and neurochemical changes occurring during adolescence in the mesocorticolimbic dopamine system. While dopamine neuron heterogeneity is increasingly appreciated at molecular, physiological, and anatomical levels, we suggest that a developmental facet may play a key role in establishing vulnerability or resilience to environmental stimuli and experience in distinct dopamine circuits, shifting the balance between healthy brain development and susceptibility to psychiatric disease.